WATER RELATIONS AT THE INITIAL SUGARCANE GROWTH PHASE UNDER VARIABLE WATER DEFICIT - Mauri,Robson (2017)
ABSTRACT This study aimed to quantify water deficit levels that compromise sugarcane initial growth exposed to different availability soil depths. The experiment was conducted in a greenhouse by using 100-liter capacity asbestos-cement boxes filled with different soil layers simulating depths of 10, 20, 30, and 40 cm. Water deficit levels were represented by accumulated reference evapotranspiration of 0, 40, 80, 120, 160, 200, 240, and 280 mm, which was considered from planting to irrigation return. Soil moisture at field capacity at planting time was sufficient to promote sprouting and emergence regardless the water deficit level that was subsequently exposed. For soil depths of 10 and 20 cm, a 160-mm water deficit level caused total plant death. On the other hand, for soil depths of 30 and 40 cm, a 200-mm water deficit level promoted plant death. A water deficit level from 40 mm significantly reduced plant growth regardless soil depth.